English Language, Globalisation and the Future of the Nigerian Indigenous Languages - Ugwu, Eucharia Okwudilichukwu (European Scientific Journal, ESJ, 2020)
In the present globalised world, languages have come to be ranked based on their roles in the world arena, the status assigned to them in the environment inwhich they are spoken as well as the number of their respective speakers. As such, some languages, including English, is considered a world language. English language wields great power in Nigeria, as an official and national language. Its ever-increasing roles have detrimental effects on the survival of the minority languages, with most of them playing just peripheral roles. Most of the minority languages are further threatened by the major ones spoken in different geopolitical zones. As the functional loads of these minority languages continue to reduce gradually and consistently, their level of vitality equally reduces. A minority language whose functional domains are overtaken by a dominant one will eventually disappear as their users shift to the latter and therefore, would no longer use them for any linguistic function. This paper discusses the current precarious situation of the Nigerian indigenous languages, especially the minority ones in the face of globalisation, the domineering effect of English language and what can be done to make these languages withstand the test of time.